Phylogenetic relationships within the subtribe Spiranthinae s.l. (Orchidaceae) inferred from the nuclear ITS region - Górniak, Marcin; Mytnik-Ejsmont, Joanna; Rutkowski, Piotr; Tukałło, Piotr; Minasiewicz, Julita; Szlachetko, Dariusz L. (Biodiversity: Research and Conservation, 2006)
Results of an analysis of ITS sequences for the subtribe Spiranthinae s.l. (Orchidaceae) are presented, and compared with results of morphological studies. To evaluate the monophyly of the subtribe, nuclear ribosomal DNA internal transcribed spacers (ITS1 and ITS2) and the 5.8S gene were sequenced for 19 taxa of the tribe Spirantheae, with Erythrodes sp., Bonatea speciosa, Cynorkis sp., Pterostylis curta and Chloraea flavescens designated as an outgroup. For 8 taxa, sequences were taken from the GenBank. The results confirmed the current subtribal position of Cyclopogoninae, with members of the subtribe forming a moderately supported clade. The unexpected occurrence of Odontorrhynchos (Spiranthinae) within the Cyclopogoninae is discussed with reference to the results of morphological studies. Although some of the genera representing the subtribe Stenorrhynchidinae Szlach. form a weakly supported clade, the remaining taxa are variously grouped with Spiranthinae representatives, receiving moderately weak bootstrap support. The results do not provide evidence for the strict monophyly of Spiranthinae s.l. and Stenorrhynchidinae.